An evaluation of proposed General Chemistry learning modules by experts and teachers - Remedel Dela Mines; Elsa Cajucom (Universitas Islam Indonesia, 2022)
This research endeavored to assess developed and validated a proposed learning module in General Chemistry during the Second Semester, Academic Year 2021-2022 in public secondary schools in Bulacan, Philippines. Teachers play an essential role in validating and evaluation of instructional materials. As facilitators of learning, they must ensure that instructional materials serve their purpose of upholding an effective teaching and learning process. The study aimed to evaluate the proposed Grade 12 General Chemistry learning modules as perceived by Chemistry Experts and Science Teachers in the 12 public secondary schools offering STEM strand in the Division of Bulacan, Philippines. The modules are evaluated based on :(1) content, (2) format, (3) presentation and organization, (4) learning activities, (5) evaluation activities and (6) accuracy and up-to-datedness of information. The demographic profile of 11 Chemistry experts showed that the majority are female, BSED graduates in Physical Science with a doctoral degree in Development Education and 1-12 years teaching General Chemistry subject. Grade 12 Chemistry teachers are mostly females who have bachelor’s degree in Physical Sciences, with master’s units and 1-5 years of teaching Grade 12 General Chemistry in the K to 12 Curriculum. Chemistry experts and science teachers assessed the five modules using descriptive survey method employing quantitative analysis. They both evaluated the proposed learning modules satisfactory in the six dimensions. They did, however, make several suggestions for improving the proposed learning module.